2007
DOI: 10.1007/s10592-006-9281-z
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic diversities in isolated populations of the Asian black bear (Ursus thibetanus) in Japan, in comparison with large stable populations

Abstract: Populations of the Asian black bear (Ursus thibetanus) are relatively large and continuous in central Honshu, the main island of Japan, but they are isolated in western Honshu. To clarify the degree of genetic isolation of the populations in western Honshu, we compared the genetic diversities of four populations in western Honshu with that of one of the continuous populations of central Honshu. Three of the four western Honshu populations were isolated and the other was continuous with the central Honshu popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 22 publications
2
14
0
2
Order By: Relevance
“…The habitat area of the Eastern Chugoku (SK), Kii Hanto (KH), and Shikoku (SK) units in western Japan are smaller than that of the WC unit. Since previous studies that examined genetic diversities of black bears by using mtDNA and microsatellite markers have suggested a lower level of genetic diversities in the populations of western Japan [6,8], MHC variation in these management units might be lower than that in the WC unit. Therefore, it is essential to investigate MHC variation in these units further by using an increased number of samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The habitat area of the Eastern Chugoku (SK), Kii Hanto (KH), and Shikoku (SK) units in western Japan are smaller than that of the WC unit. Since previous studies that examined genetic diversities of black bears by using mtDNA and microsatellite markers have suggested a lower level of genetic diversities in the populations of western Japan [6,8], MHC variation in these management units might be lower than that in the WC unit. Therefore, it is essential to investigate MHC variation in these units further by using an increased number of samples.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of the mtDNA control region indicated that the Japanese black bear could be divided genetically into three groups: western, eastern, and Shikoku/Kii-hanto populations [7,8]. Analyses of mtDNA and microsatellite markers [6,8] revealed lower genetic diversity and higher genetic differentiation in the western population than in the other populations. In fact, in most of the management units in western Japan the species has been designated as “endangered” in the Red Data Book of Japan [13] because of the fragmentation and isolation of their habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Such low genetic diversity could be caused by decreases in population size, population extinction, genetic drift, and habitat loss (Allentoft and Brien, 2010); factors that have been discussed previously in relation to amphibians (Murphy et al, 2000). Furthermore, some studies have proposed that isolated populations may have low genetic variation (Ohnishi et al, 2007). Urban development has also been a major cause of fragmented habitats.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Demographic analysis can provide information on population trends and the life stages or sex most impacted by stressors (Dorcas et al 2007;Tatin et al 2009), while genetic analysis can quantify existing levels of genetic diversity and the timing of historic bottlenecks (Ramakrishnan et al 2005;Ohnishi et al 2007;Dixo et al 2009;Meyer et al 2009;Fluker et al 2010). However, recent demographic bottlenecks may not be accompanied by declines in genetic diversity in long-lived species; specifically, long generation time is thought to buffer reductions in genetic diversity (Kuo and Janzen 2004).…”
Section: Introductionmentioning
confidence: 99%